2005
DOI: 10.1177/1049731505277947
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment and the Justice System: Predictors of Court Involvement

Abstract: Objectives: Characteristics of the child victim, perpetrator, and maltreatment incident were used to examine predictors of court involvement in cases of serious child maltreatment. Method: Cases were drawn from those reported to: child protective services (n = 225), sheriff's office ( n = 225), prosecutor's office ( n = 60), and dependency court ( n = 65). Logistic regression was used to calculate predicted probabilities of criminal court involvement and dependency court involvement Results: Cases involving fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…The results of this study also lend support to earlier studies suggesting that police are more likely to lay charges if the harm or maltreatment suffered by 440 the child is severe or results in injury (Brewer et al, 1997;Cross et al, 1994Sedlak et al, 2005;Stroud et al, 2000). It has been stated that police lay charges only in cases where there is a high probability of securing a conviction to avoid making wrongful prosecutions (Holleran et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The results of this study also lend support to earlier studies suggesting that police are more likely to lay charges if the harm or maltreatment suffered by 440 the child is severe or results in injury (Brewer et al, 1997;Cross et al, 1994Sedlak et al, 2005;Stroud et al, 2000). It has been stated that police lay charges only in cases where there is a high probability of securing a conviction to avoid making wrongful prosecutions (Holleran et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…The extant literature has consistently found that police charging decisions are higher for sexual abuse cases (Brewer et al, 1997;Bryden & 430 Lengnick, 1997;Cross et al, 2005Cross et al, , 2015Sedlak et al, 2005;Walsh et al, 2010). This finding may be because child sexual abuse includes using children younger than age 16 years for all types of sexual activity, from sexual touching to prostitution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in children’s victimization experiences may affect how they are prepared for legal involvement and what is expected of them during legal proceedings. Finally, criminal prosecution is less likely when victims are younger (Sedlak et al, 2005; Whitcomb et al, 1991), which may lead to proportionally more older children being represented in criminal than dependency court.…”
Section: Introductionmentioning
confidence: 99%